1988
DOI: 10.1002/actp.1988.010390715
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic relaxation in polypropylene fibres

Abstract: Three types of drawn PP fibres have been investigated by nuclear magnetic relaxation methods. The two minima observed in both the temperature dependence of T, and Tzeff are related to the well known pand a-processes, respectively.The results of the experiments show that in particular the crystalline regions are influenced by drawing. Kernmagmtische Relaxation in PolypropylenfasernMit Hilfe der kernmagnetischen Relaxation wurden drei Typen gereckter PP-Fasern untersucht. Die beiden Minima in den Temperaturabhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It was reported that the drawing increases macromolecular orientation in crystalline and non-crystalline regions, which results in the increase of the optical birefringences Dn [8]. We suppose that the shift of the temperature T min is connected to the restriction of the segmental motion arising from the higher macromolecular orientation in non-crystalline regions of the polymer under study [3]. The increase of the relaxation times T 1, min with increased drawing ratio k can be related to the change of crystallinity of the drawn fibers.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…It was reported that the drawing increases macromolecular orientation in crystalline and non-crystalline regions, which results in the increase of the optical birefringences Dn [8]. We suppose that the shift of the temperature T min is connected to the restriction of the segmental motion arising from the higher macromolecular orientation in non-crystalline regions of the polymer under study [3]. The increase of the relaxation times T 1, min with increased drawing ratio k can be related to the change of crystallinity of the drawn fibers.…”
Section: Resultsmentioning
confidence: 80%
“…In partially crystalline polymers the values of the spin -lattice relaxation times T 1, min are determined not only by the spin -lattice relaxation but also, due to the spin diffusion, by the relative amount of the non-crystalline (relaxing) polymer chains. It was reported that an increase of the crystallinity gives rise to an increase of T 1, min [3,9]. The values of crystallinity X c , optical birefringence Dn, temperatures T min and relaxation times T 1, min are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation